Tuning cell death and inflammation in parkinson's disease - Dionísio, Pedro A. (2023)
Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide, and the motor deficits usually associated with the disorder correlate with dopaminergic neurodegeneration in the substantia nigra (SN) and striatum. Although apoptosis is considered the main neurodegenerative mechanism in PD, it was recently shown that necroptosis can also play a role in neuronal loss. Necroptosis is a regulated form of necrosis which depends on receptor interacting protein 3 (RIP3), being negatively regulated by caspase-8 activity. Interestingly, RIP3 also appears to exert non-necroptotic roles in apoptosis and inflammation. Parkin, a ubiquitously expressed E3 ubiquitin ligase whose loss-of-function mutations lead to early onset familial forms of PD, has also been implicated in neurodegenerative processes. Moreover, parkin can participate in multiple ubiquitination events involved in necroptosis and inflammation. The main objectives of this work were to evaluate the role of necroptosis in dopaminergic neurodegeneration in PD, and to study the influence of parkin during inflammation and necroptosis in microglia. Firstly, we characterized the molecular mechanisms involved in necroptosis induced by several stimuli in microglial BV-2 and N9 cells lines, as well as in primary microglia, upon pharmacological caspase inactivation with the pan-caspase inhibitor zVAD.fmk (zVAD). Necroptosis was also dependent on RIP1 kinase activity in these conditions. Unexpectedly, parkin knockdown strongly protected BV-2 cells from zVAD-mediated necroptosis and upregulation of pro-inflammatory genes, which was correlated with higher RIP1 ubiquitination levels in these cells, suggesting that parkin loss-of-function may increase RIP1 pro-survival ubiquitination, at least in this experimental setting. Conversely, parkin silencing increased the expression of pro-inflammatory genes in BV-2 and primary microglia exposed to different pro-inflammatory stimuli. In the case of BV-2 cells, this increase in the pro-inflammatory response following lipopolysaccharide (LPS) exposure was dependent on NF-κB/JNK over-activation. In our second study, we evaluated the role of necroptosis in dopaminergic neurodegeneration in wild-type (Wt) and RIP3 knockout (ko) mice exposed to the selective neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), widely used to induce nigrostriatal degeneration in experimental models of PD. Importantly, MPTP-lesioned RIP3ko mice were significantly protected from neuronal cell loss in the SN, although this protection was probably independent on necroptosis, since no markers of necroptosis were detected in MPTP-exposed Wt mice at several time-points. Moreover, MPTP-lesioned Wt mice presented DNA fragmentation, caspase 3 activation, lipid peroxidation and BAX expression in the SN, along with absent caspase 8 activation, suggesting a role for intrinsic apoptosis in neuronal loss. These markers of cell damage/death were also detected in primary cortical neuronal cultures exposed to the active metabolite of MPTP, MPP+. Importantly, RIP3 deletion limited cell loss and appearance of these cell death markers in both cultured neurons and the SN of mice. Interestingly, striatal astrogliosis was highly exacerbated in MPTP-injected RIP3ko mice when compared to Wt, along with absence of microgliosis and reposition of the levels of glial cell line-derived neurotrophic factor (GDNF), a potent dopaminergic neurotrophin, suggesting a role for RIP3 in MPTP-driven inflammation. In conclusion, our studies highlight how parkin and RIP3 can participate in still poorly characterized inflammatory and cell death pathways to fine-tune the cellular response, which may be relevant in pathological settings, including PD. Our results suggest that parkin loss-of-function can directly contribute to chronic inflammation in PD by promoting the survival and pro-inflammatory activities of stimulated microglia. Moreover, RIP3 may exert non-necroptotic functions in inflammation and MPTP-dependent apoptosis. These functions may depend on RIP3 scaffolding properties with no involvement of its kinase activity, and further characterization of these dual aspects can lead to a more specific therapeutic targeting of this protein in multiple disorders.